Integration of High‐Frequency M‐Type Hexagonal Ferrite Inductors in LTCC Multilayer Modules. Issue 3 (15th December 2015) - Bierlich, Silvia; Reimann, Timmy; Barth, Stefan; Capraro, Beate; Bartsch, Heike; Müller, Jens; Töpfer, Jörg
Abstract : Monolithic hexagonal BaCo1, 3 Ti1, 3 Fe9, 4 O19 ferrite multilayers sintered at 900°C exhibit a fine‐grained microstructure with permeability of μ′ = 16 and a resonance frequency f r ≥ 1GHz. Co‐firing of hetero‐laminates of ferrite with CT700 glass–ceramic LTCC tapes and with polycrystalline zinc titanate (ZT) LTCC tapes was studied. Co‐firing at 900°C of ferrite/CT700 leads to multilayers with cracks caused by substantial thermal expansion mismatch. Co‐fired ferrite/ZT multilayer laminates exhibit a permeability of μ′ = 16 and do not show any defects. Hexagonal ferrite multilayer inductor elements were integrated into ZT‐based multilayer LTCC modules and co‐fired at 900°C with Ag metallization.